Polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in the Grenlandfjords (Norway)--disposition, levels, and effects - Ruus, Anders; Berge, John Arthur; Hylland, Ketil; Bjerkeng, Birger; Bakke, Torgeir; Naes, Kristoffer (Journal of toxicology and environmental health. Part A, 2006)
Polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) are regarded as highly toxic. Their lipophilicity and persistence also render them subject to bioaccumulation. The Grenlandfjords (southern Norway) have long been polluted by PCDD/Fs through the magnesium production at Herøya (1951-2002). Therefore, extensive environmental monitoring was performed in the area, and the project "Dioxins in the Grenlandfjords--DIG" was launched to study abiotic mass balances, biotic processes and ecological risk. This article describes some results from DIG on the dispositions of PCDD/Fs in the food web and biological effects. Furthermore, data from the Norwegian monitoring of the Grenlandfjords are described. Differences in cod liver PCDD/F levels were found between stations, with the highest concentrations in the inner fjord (the Frierfjord), closest to the pollution source. Furthermore, considerable decreases in the concentrations followed the large discharge reductions (1975 and 1990). Contrary to earlier food web studies on other organochlorines, it was found that the concentrations of PCDD/Fs decline with higher trophic level. Higher chlorinated congeners also constituted a lower percentage of sigmaPCDD/Fs higher in the food chain. The results indicated a limited bioaccumulation of PCDD/Fs, especially of higher chlorinated congeners, likely due to reduced membrane permeability (high molecular size), and possibly slow transport through intestinal aqueous phases. Hepatic cod 7-ethoxyresorufin O-deethylase (EROD) activities differed between the Frierfjord and the Eidangerfjord, showing the different PCDD/F exposure in the two fjords. Furthermore, seasonal variations in cytochrome P-450 (CYP) 1A activity were shown, with different responses between genders. The differences were likely linked to the reproductive cycle of the fish.